Prothrombine and activated partial thromboplastin time are prolonged in hepatic cirrhosis - Limijadi, Edward Kurnia Setiawan; Suromo, Lisyani Budi; Budiwiyono, Imam (Universa Medicina, 2016)
BackgroundChronic hepatitis and hepatic cirrhosis are chronic liver diseases that cause disorders of liver function, such as the formation of platelets and coagulation factors (prothrombin time/PT and activated partial thromboplastin time/APTT). Chronic hepatitis in the long term can develop into hepatic cirrhosis. The aim of this study was to determine platelet count, PT, and APTT as indicators in the progression of chronic hepatitis towards hepatic cirrhosis. MethodsA cross-sectional study was conducted on 50 patients with chronic hepatitis and hepatic cirrhosis in Semarang City Regional General Hospital, Telogorejo Hospital and Kariadi General Hospital. The platelet count was measured with a Sysmex XP-100, while PT and APTT was measured with a Sysmex CA-1500 coagulometer. The Mann Whitney test was applied to analyze the difference in platelet count, PT, and APTT between chronic hepatitis and hepatic cirrhosis. Results Median, minimum, and maximum values of platelet count, PT and APTT in chronic hepatitis were 284.000/µl, 210.000/µl, 390.000/µl; 10.6 sec, 9.5 sec, 13.6 sec; and 30.5 sec, 24.2 sec, 46.4 sec, respectively, and in hepatic cirrhosis they were 96.300/µl, 48.200/µl, 133.800/µl; 27.5 sec, 11.9 sec, 44.7 sec; and 55.6 sec, 31.3 sec, 72.0 sec, respectively. There was a significant difference the reduction of platelet count, and the prolongation of PT and APTT in chronic hepatitis compared to hepatic cirrhosis (p=0.000). ConclusionsProthrombine time and APTT were prolonged and platelet count was decreased in hepatic cirrhosis subjects. The three parameters may be used to evaluate the progression of chronic hepatitis towards hepatic cirrhosis.